42+x=60+4x

Simple and best practice solution for 42+x=60+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42+x=60+4x equation:



42+x=60+4x
We move all terms to the left:
42+x-(60+4x)=0
We add all the numbers together, and all the variables
x-(4x+60)+42=0
We get rid of parentheses
x-4x-60+42=0
We add all the numbers together, and all the variables
-3x-18=0
We move all terms containing x to the left, all other terms to the right
-3x=18
x=18/-3
x=-6

See similar equations:

| 3a+7-4=23 | | -1=7u+5/6-6u+9/5 | | -17v+5v=-65-7 | | 5x/4=7.5 | | X-3/2-x+1/3=2x | | X+1/2=2/3+x | | 3a+4=5a−8 | | -4x+1=3(5x-4)-6 | | 2(2x-3)-7=-9 | | -44=5(x-2)+1 | | 4x-15=-4x+57 | | 2(3x+4)-8=36 | | 3x+2=9-5x | | √y+10=y+10 | | 2x+4=44−2x | | 12k=97 | | 1/2x+2/3=8 | | 5z+0=25 | | 3y+21=33 | | 0.4(3x-1)=0.5(x+1) | | a^2=3a+8 | | 60+2x=120–x | | 60+2x=120–x, | | 3x–57=88 | | 15p^2+5p=20 | | 15^2p+5p=20 | | 2/3x-5=4+x | | (x+9)/5=-9 | | 18-4y=10 | | (7)(17.5)=3x | | -3(3p+6)-2(2-14p)=3(4+6p) | | -5(-2x+8)-8(-5-5x)=48+51x |

Equations solver categories